VIOLENT PROTEST AT LOCAL GOVERNMENT LEVEL IN SOUTH AFRICA: REVOLUTIONARY POTENTIAL? - Hough, Mike (Scientia Militaria - South African Journal of Military Studies, 2011)
In this article, a broad overview of the main causes and theories of revolution is presented. The objective is to obtain, by analysing recent events in South Africa pertaining to the ongoing protest actions over service delivery at local government level, some indication of revolutionary potential in South Africa. In this regard, there seem to be two basic views, namely on the one hand, that violent protest action at local level can lead to revolutionary activity, and on the other hand, that the protest can be contained but aspects of policy will have to be adapted.